Determination of copper and zinc levels insome cereals in the local market - Salman, Fouad (Latakia University Journal -Biological Sciences Series, 2013)
The concentrations of copper (Cu) and zinc (Zn) in samples of some cereals available at local markets in Syria weredetermined, after nitric digestion, using Atomic Absorption Spectrometry. The study showed that the heavy metals were present in all samples at different levels. The concentration of heavy metals varied from trace to higher concentration. The maximum level of copper (Cu) in the cereal samples was 0.426 mg kg-1 on dry weight basis, where the maximum level of zinc (Zn) in the cereal samples was 2.325mg mg kg-1 on dry weight basis. The analytical results obtained for the heavy metals indicate that the copper and zinc were present in all samples at concentration well below the acceptable concentration recommended by the World Health Organization.